Pembelajaran Berbasis Masalah untuk Konsep Perkalian: Integrasi Progresivisme di Sekolah Dasar - Mariana Jediut; Fransiska Jaiman Madu; Yohannes Marryono Jamun; Zephisius Rudyanto Eso Ntelok (Science and Education Journal (SICEDU), 2026)
Multiplication is a fundamental concept in elementary school mathematics. However, it is still often learned as the memorization of number facts and calculation procedures, rather than as a concept of equal grouping, repeated addition, row-column arrangements, or contextual problem solving. This article aims to describe the implementation of problem-based learning to strengthen elementary school students’ understanding of multiplication concepts and to explain the integration of progressivist principles in each phase of problem-based learning. This study used a thematic narrative literature review method. Relevant journal articles, proceedings, books, and policy documents, particularly those published between 2015 and 2025, were searched through Google Scholar and national and international journal portals using the keywords problem-based learning, progressivism, conceptual understanding, and elementary school multiplication. The data were analyzed through thematic coding and synthesis. The findings show that problem-based learning supports multiplication learning when it begins with authentic problems, followed by small-group investigation, the use of various representations, presentation of results, concept consolidation, reflection, and application. Progressivist principles strengthen this process through learning by doing, student-centered inquiry, collaboration, contextual learning, and reflection on experience. Thus, the integration of problem-based learning and progressivism can serve as both a pedagogical and philosophical framework for designing meaningful multiplication learning in elementary schools.